Small states, Russia and the West : polarity, constellations and heterogeneity in the geopolitics of the Caucasus - Abrahamyan, Eduard (Routledge, Taylor & Francis Group, 2025)
This book offers an in-depth investigation of the contemporary geopolitics of the Caucasus through a multi-level analysis of regional political transformations. It delves into the contrasting foreign policies of small states in the Caucasus in response to the Russian interventions in Georgia in 2008 and Ukraine in 2014 and 2022, which marked Russia's 'return' as an order-forming power, challenging the agenda of Euro-Atlantic integration. The author expands and adapts Constellation Theory to examine emerging non-Western regional orders, using a relational polarity framework to argue that the choices of Armenia, Azerbaijan, and Georgia are not merely products of Russian or Western influence but are shaped by each state's unique geocultural propensities, distinct asymmetric relationships with divergent power poles, and differing perceptions of reality. This book enriches the emerging discourse on the regional complexities of the multipolar world order with multifaceted interpretations of politics and decision-making through its nuanced regional focus and innovative theoretical grounding. It contributes significantly to International Relations theory, geopolitics, small-states and area studies, offering invaluable insights into small-state foreign policy dynamics in the age of rising global multipolarity.
Keywords: Geopolitics -- Caucasus, South.; States, Small.; Caucasus, South -- Politics and government -- 1991-; Caucasus, South -- Foreign relations -- 1991-; Caucasus, South -- Foreign relations -- Russia (Federation); Russia (Federation) -- Foreign relations -- Caucasus, South.; Russia; Aremenia; Georgia; Ukraine; Constellation Theory; Azerbaijan; elektronické knihy; electronic books